Gas desorption characteristics effected by the pulsating hydraulic fracturing in coal - Guanhua, Ni; Kai, Dong; Shang, Li; Qian, Sun (Fuel (Guildford), 2019)
In order to clarify the effect of pulsating fracturing on gas comprehensive desorption, experimental study of gas desorption characteristics effected by the pulsating hydraulic fracturing (PHF) and static hydraulic fracturing (SHF) were carried out, the gas displacement amount (GDA) and natural desorption amount (NDA) under different hydraulic fracturing methods are investigated. The results show that the GDA generated by the SHF is significantly less than the PHF. At the same time, the GDA increases linearly first, and then logarithmically with the fracturing frequency; with the increase of pulsating peak pressure, it showed a logarithmic increase. The water has an inhibitory effect on the natural desorption of gas. With the increase of pulsating pressure and frequency, the effect of pulsation fracturing suppressing the natural desorption of gas is weakened. According to the effect of different fracturing methods on gas desorption, the PHF is divided into four types: low pressure-low frequency, low pressure-high frequency, high pressure-low frequency and high pressure-high frequency. Because the gas displacement rate (ƞd) determines the changes of gas comprehensive desorption effect, the low pressure-low frequency inhibits gas desorption, while the low pressure-high frequency, high pressure-low frequency and high pressure-high frequency can promote gas desorption. The results provide theoretical guidance for optimizing pulsating parameters, increasing gas desorption and promoting coal seam gas drainage.